Investigation of the protective effects of intraperitoneal melatonin in rats receiving laryngeal radiotherapy. Issue 3 (June 2023) - Dündar, Görkem; Günaydın, Önder; Yazıcı, Gözde; Kurtulan, Olcay; Öğüş, Elmas; Şahin, İbrahim
Abstract: Objectives: To examine the protective effects of melatonin on laryngeal radiation damage. Materials and methods: 31 rats were divided into 4 groups as follows: 1) the control (C) group (n=7), was only injected with intraperitoneal ethanol solution; 2) the melatonin (M) group (n=8), was injected intraperitoneal melatonin solution with 5 mg/kg; 3) the radiotherapy (RT) group (n=8) was given laryngeal radiation after intraperitoneal injection of ethanol solution; 4) the M + RT group (n=8), RT was given 30 minutes after 5 mg/kg dose of melatonin solution was injected. Drug and radiation applications were continued for 5 days. The weight changes of the rats were recorded. At the end of the study, inflammation, neutrophil migration and lymphoid aggregates, collagen distribution, laryngeal glandular structures and biochemical analysis of laryngeal tissues [malondialdehyde (MDA), total oxidant status (TOS) and total antioxidant status (TAS)] were determined. Results: In the M+RT group, the first day and the 30th weight differences were significantly increased when compared with the RT group (p=0.050). Inflammation, neutrophil migration, lymphoid aggregate, disorganized collagen distribution and loss of glandular tissues were found statistically more in the RT group than in the C group (p<0.05). MDA and TOS levels were in the M + RT group exhibited better values than they did in the RT group (p<0.05). TAS levels was markedly increased in the M + RT group than in the RT group (p<0.001). Conclusion: Administration of melatonin to rats prior receiving laryngeal radiation, decreases the level of oxidative stress markers and increases the level of anti-oxidative markers.